Wellness in contemporary sport - Kunysz-Rozborska, Magdalena (Journal of Education, Health and Sport, 2017)
For a long time sport manifests itself in many different forms, accompanies man in everyday life. Many sports go back to the distant past, when physical fitness ensured survival. We are now living in times when it is impossible to miss sports that play so many important roles in society. Amateur and professional sports become a common form of leisure. correct methods of wellness. The purpose of my article is to show the phenomenon and factors accompanying it. Biological renewal is the impact on the body of various natural and artificial resources and environmental conditions in order to accelerate physiological resting processes. Nowadays, it is an escape from everyday life, stress, fatigue. Unfortunately, not everyone knows and understands how long the journey is for sports success, commitment and dedication from athletes and their trainers and the entire staff of people playing more or less important roles in the athletes’ career. To achieve ambitious plans, the optimal training load should be determined, keeping in mind primarily the athlete’s health, since no body will tolerate intensity, even moderate, unless he rests and regenerates. It is difficult to imagine professional training without proper and systematic conduct of renewal. There is a growing demand for professionals looking for new ways to improve athletes and use the correct methods of wellness. The purpose of my article is to show the phenomenon and factors accompanying it. Biological renewal is the impact on the body of various natural and artificial resources and environmental conditions in order to accelerate physiological resting processes.